A qualitative research on emotion regulation processes and expressive language skills in kindergarten: a case study - Oğuz, Sena Nur; Pınar, Yunus (Frontiers in Psychology, 2025)
This single-case study focused on Aylin (name anonymized), a typically developing five-year-old girl, observed over 9 months following her kindergarten enrollment. Using the Tavistock Child Observation Model, videography, HAVAS 5 language screening, and semi-structured parental interviews, the study examined her social interaction, emotion regulation, and expressive language development. Aylin experienced marked anxiety and stress, especially during the adjustment phase, struggling with separation from her parents and the unfamiliar school environment. Initially withdrawn, she gradually developed strategies to engage with peers and seek inclusion in group activities. Emotional security was a key factor in her ability to play cooperatively and express herself more fluently. HAVAS 5 results reflected notable progress in her expressive language skills by the end of the year. Parental interviews revealed that Aylin had spent over a year in pandemic-related isolation starting at age two and a half, limiting her social and physical development. Both parents cited challenges in offering consistent interaction, which may have shaped Aylin’s early difficulties. The findings underscore the interconnectedness of emotional regulation, symbolic play, and language expression, emphasizing the value of emotionally responsive early education.